A Novel Model for Efficient Communication in 2g/2.5g Or 3g Through Reduced Signalling Overhead (International Journal of Scientific Research and Management (IJSRM), 2013)
With its great features like providing access to users at anytime and anywhere in the world, mobile communication has been very attractive among the users as well as operators and service providers. However, despite of several advantages,mobile communication has also been facing many safety problems. In 2G/2.5G (GSM, GPRS) and 3G (UMTS) technologies, the architectures comprise of mainly three nodes; the mobile station (MS), Visitor Location Register/Serving GPRS support Node (VLR/SGSN), and Home Location Register (HLR). These nodes are involved to encode/decode the data and validate theuser (MS) in 2G and 3G. To add more and more protected features, we propose a new generalized approach in this paper which is based on reduced signaling overhead.